Do organization-level quality management systems influence department-level quality? A cross-sectional study across 32 large hospitals in Australia. (5th February 2020) - Taylor, Natalie; Clay-Williams, Robyn; Ting, Hsuen P; Arnolda, Gaston; Winata, Teresa; Hogden, Emily; Braithwaite, Jeffrey
Abstract: Objective: Little is known about the influence that hospital quality systems have on quality at department level, in Australia and elsewhere. This study assessed the relationships between organizational-level quality management systems, and the extent to which hospital-level quality management systems and department-level quality management strategies are related. Design: A multi-level, cross-sectional, mixed-method study. Setting and participants: As part of the Deepening our Understanding of Quality in Australia (DUQuA) project, we invited all large hospitals in Australia (~200 or more beds) which provided acute myocardial infarction (AMI), hip fracture and stroke care. The quality managers of these hospitals were the respondents for one of seven measures of hospital quality management systems and strategies. Data across the six remaining measures were collected through site visits by external surveyors assessing the participating hospitals. Main outcome measures: Relationships were assessed between three organization-level quality management system measures: a self-report measure assessing organization-level quality activities (quality management systems index, QMSI); externally assessed organization-level compliance to procedures used to plan, monitor and improve quality of care (quality management compliance index, QMCI); and externally assessed implementation of quality systems (clinical quality implementation index, CQII). Associations were also assessed between organization-level quality management systems and department-level quality management strategies: how clinical responsibilities are assigned for a particular condition; whether department organization processes are organized to facilitate evidence-based care recommendations; compliance with selected recommendations of international agencies; and whether clinical reviews are performed systematically. Results: Of 78 invited hospitals, 32 participated in the study. QMSI was positively associated with QMCI and CQII, but after controlling for QMSI, no relationship was found between QMCI and CQII. There appears to be a cluster of relationships between QMSI and department-level measures, but this was not consistent across all departments. Conclusion: This is the first national study undertaken in Australia to assess relationships within and between organization-level and department-level quality management systems. These quality management system tools align with many components of accreditation standards and may be useful for hospitals in continuously monitoring and driving improvement.